PALE SOILS ON CARBONATE-FREE DEPOSITS IN CENTRAL SIBERIA AND THEIR TAXONOMIC POSITION IN THE SOIL CLASSIFICATION OF RUSSIA - T. V. Ananko; M. I. Gerasimova; D. E. Konyushkov (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
Based upon a comprehensive analysis of detailed descriptions of soil profiles and analytical data obtained by I. Sokolov, V. Zolnikov, L. Yelovskaya and other researchers, as well as upon data on the soil-forming factors, an attempt is made to determine the taxonomic level of pale undifferentiated neutral and slightly acid soils derived from carbonate-free deposits in the new classification system of Russian soils (versions 2004, 2008). The above group of soils is not uniform. According to their diagnostic morphological and physical-chemical properties the loamy permafrost-affected soils with ice-rich permafrost should be placed in the order of cryometamorphic or iron-metamorphic soils. The loamy sandy soils with dry permafrost may be placed in the same order. The soils with a shallow profile (< 30 cm) on hard parent rock should be qualified as members of the order of lithozems. The specific features of these soils make it possible to suggest new elements to the soil classification. A subtype of pale-metamorphized soils is offered to recognize the types of rzhavozems and raw-humus rzhavozems as the soils transitional to the pale soils. This suggestion is aimed at harmonization of a variety of ideas on the genesis, conditions for the development and nomenclature of soils, which permits us to give a more complete and reliable perception of the soil cover in the Central Siberian plateau.